A Novel QTL Conferring Fusarium Crown Rot Resistance Located on Chromosome Arm 6HL in Barley - Gao, Shang; Zheng, Zhi; Hu, Haiyan; Shi, Haoran; Ma, Jian; Liu, Yaxi; Wei, Yuming; Zheng, You-Liang; Zhou, Meixue; Liu, Chunji (Frontiers in Plant Science, 2019)
Fusarium crown rot (FCR), caused primarily by Fusarium pseudograminearum, is a devastating disease for cereal production in semi-arid regions worldwide. To identify and characterize loci conferring FCR resistance, we assessed a landrace AWCS799 which is among the best lines identified from a systematic screening of more than 1,000 genotypes. Genetic control of its resistance was investigated by generating and analysing two populations of recombinant inbred lines with AWCS799 as the common parent. One of the populations was used for QTL detection and the other for validation. A novel QTL, located on the long arm of chromosome 6H (designated as Qcrs.caf-6H), was consistently detected in each of the four FCR severity tests conducted against the mapping population. The QTL explained up to 28.3% of the phenotypic variance and its effect was confirmed in the validation population. Significant interaction between this resistance locus and either plant height or heading date was not detected, further facilitating its manipulation in breeding programs.